Analysis of DMU40 machine centre by vibration measurement - Kiss, Róbert; Szilágyi, Attila (Design of Machines and Structures, 2020)
This article is part of a longer research-analytical work, because it outlines the results and conclusions of the study according to the main topic of the research and the applied method. The central theme of the research is the dynamic stiffness of machine tools and the various methods for their determination. Following analytical analysis the machine tool natural frequencies were determined using a finite element software (ANSYS Workbench R19.1), which we now approach from a practical point of view, that is determined in the workshop by measurements. The results obtained are compared for each of the three methods.